2019
DOI: 10.1249/mss.0000000000002156
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cuff Pressure on Blood Flow during Blood Flow–restricted Rest and Exercise

Abstract: The purpose of this study was to investigate the blood flow/pressure relationship (linear or nonlinear) in the superficial femoral artery when seated, as well as to investigate blood flow changes with exercise using varying cuff pressures and a preexercise (PE) condition. The presence of venous outflow with occlusion at rest and exercise was also investigated. Methods: Twenty-three subjects visited the lab on 3 occasions. First to determine linearity of blood flow using 0% to 90% arterial occlusion pressure (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 34 publications
1
42
1
Order By: Relevance
“…In the former study, as the external pressure applied on the thigh increased from 0% to 100% of occlusion pressure, blood flow and mean blood velocity in the posterior tibial artery decreased in a linear manner [ 26 ]. In contrast, Crossley et al [ 28 ] reported a non-linear decline in muscle blood flow characterized by an abrupt rate of decline in muscle blood flow as the occlusion pressure increased from 80% to 100%. One point relevant to our study is that, to our best knowledge, no data exist on the relationship between different levels of occlusion pressure and muscle blood flow while exercising with relatively large muscle groups.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In the former study, as the external pressure applied on the thigh increased from 0% to 100% of occlusion pressure, blood flow and mean blood velocity in the posterior tibial artery decreased in a linear manner [ 26 ]. In contrast, Crossley et al [ 28 ] reported a non-linear decline in muscle blood flow characterized by an abrupt rate of decline in muscle blood flow as the occlusion pressure increased from 80% to 100%. One point relevant to our study is that, to our best knowledge, no data exist on the relationship between different levels of occlusion pressure and muscle blood flow while exercising with relatively large muscle groups.…”
Section: Discussionmentioning
confidence: 97%
“…The similarity in TSI decline between MI-BFR and HI may indicate a similar level of muscle hypoxia between the two conditions despite the fact that exercise intensity is much lower in the former (40% P peak ) compared to the latter (70% P peak ). Previous studies have shown a decline in muscle blood flow as a result of external pressure application [ 26 , 28 ]. In the former study, as the external pressure applied on the thigh increased from 0% to 100% of occlusion pressure, blood flow and mean blood velocity in the posterior tibial artery decreased in a linear manner [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations